Pemberian Kompos Kulit Buah Kakao Pada Medium Ultisol Untuk Pertumbuhan Bibit Kakao (Theobroma cacao L) - Juniadi Naibaho; Nelvia Nelvia; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to study the effect of cocoa fruit skin compost (CFSC) on Ultisol medium the growth of cocoa seed. This research was conducted in experiment garden of Faculty of Agriculture, University of Riau, at Bina Widya Campus, Subrantas Street km 12.5, Simpang Baru, Tampan, Pekanbaru. This research taken time as 3 months starting from june 2016 until October 2016. This experiment was conducted used Randomized Complete Design (RCD) non factorial is cocoa fruit skin compost (CFSC) consist of 6 level (0, 50, 100, 150, 200 and 250 g cfsc/plant) with 3 replications. Observation parameters consist of seed height, number of leaves, stem diameter, canopy dry weight, dry weight of root and root canopy ratio. The result of this research show that the applications 200 g cfsc/plant increased seed height, number of leaves, stem diameter, canopy dry weight, dry weight of root and root canopy ratio compared with without applications. Keywords: Cocoa Seeds, cocoa fruit skin compost, Ultisol Soil